A Single Amino Acid Substitution in IIIf Subfamily of Basic Helix-Loop-Helix Transcription Factor AtMYC1 Leads to Trichome and Root Hair Patterning Defects by Abolishing Its Interaction with Partner Proteins in Arabidopsis - Zhao, Hongtao (American Society for Biochemistry and Molecular Biology, 2012)
Plant trichomes and root hairs are powerful models for the study of cell fate determination. In Arabidopsis thaliana, trichome and root hair initiation requires a combination of three groups of proteins, including the WD40 repeat protein TRANSPARENT TESTA GLABRA1 (TTG1), R2R3 repeat MYB protein GLABRA1 (GL1), or WEREWOLF (WER) and the IIIf subfamily of basic helix-loop-helix (bHLH) protein GLABRA3 (GL3) or ENHANCER OF GLABRA3 (EGL3). The bHLH component acts as a docking site for TTG1 and MYB proteins. Here, we isolated a mutant showing defects in trichome and root hair patterning that carried a point mutation (R173H) in AtMYC1 that encodes the fourth member of IIIf bHLH family protein. Genetic analysis revealed partial redundant yet distinct function between AtMYC1 and GL3/EGL3. GLABRA2 (GL2), an important transcription factor involved in trichome and root hair control, was down-regulated in Atmyc1 plants, suggesting the requirement of AtMYC1 for appropriate GL2 transcription. Like its homologs, AtMYC1 formed a complex with TTG1 and MYB proteins but did not dimerized. In addition, the interaction of AtMYC1 with MYB proteins and TTG1 was abrogated by the R173H substitution in Atmyc1-1. We found that this amino acid (Arg) is conserved in the AtMYC1 homologs GL3/EGL3 and that it is essential for their interaction with MYB proteins and for their proper functions. Our findings indicate that AtMYC1 is an important regulator of trichome and root hair initiation, and they reveal a novel amino acid necessary for protein-protein interactions and gene function in IIIf subfamily bHLH transcription factors.